2015
DOI: 10.1111/papr.12291
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain Components in Patients with Cancer: Prevalence, Treatment, and Interference with Daily Activities

Abstract: This study shows that over 40% of the patients with moderate to severe pain also have neuropathic symptoms, causing increased interference with daily activities. Most of these patients do not receive adjuvant analgesics. There is a need to improve management of neuropathic symptoms in patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
28
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 38 publications
8
28
1
5
Order By: Relevance
“…However, the current results have not found a significant statistical association between the presence of this symptom and gender, and neither between the presence of the symptom and different age brackets. This study did not see any association between NP and the types of treatments performed, different from other studies that suggested a greater association of neuropathic harm for those people subjected to chemotherapy 8,15 . However, there was no appraisal of the chemotherapy schemes that knowingly affect the risk of dysfunction of the central nervous system 6,8,10 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, the current results have not found a significant statistical association between the presence of this symptom and gender, and neither between the presence of the symptom and different age brackets. This study did not see any association between NP and the types of treatments performed, different from other studies that suggested a greater association of neuropathic harm for those people subjected to chemotherapy 8,15 . However, there was no appraisal of the chemotherapy schemes that knowingly affect the risk of dysfunction of the central nervous system 6,8,10 .…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, despite some inconsistencies in the literature, the reported incidence of the individual items of each diagnostic test are in accordance with our data …”
Section: Discussionsupporting
confidence: 91%
“…The DN4 and painDETECT questionnaires were initially developed for the detection of neuropathic pain in noncancer patients and are currently used extensively in outpatient cancer patients . The DN4 questionnaire was originally validated in the French population .…”
Section: Discussionmentioning
confidence: 99%
“…33 Our present study findings demonstrated a very strong association between cancer pain with an NPC and all BPI measures of pain intensity and were consistent with the findings of other recent studies. 32,34,35 Surprisingly, with the exception of relations with people, the BPI interference items were not associated with an NPC. It should be noted that although the group with an NPC had a higher MEDD at referral, the MEDD of the entire study sample was comparatively low, likely reflecting an under use of opioids, which in turn may contribute to higher pain intensity levels.…”
Section: Discussionmentioning
confidence: 86%
“…37 Pain duration of three or more months was predictive of an NPC; both clinical experience and a report suggests that chronicity is often a feature of neuropathic pain, 35 albeit that chronicity may also reflect under treatment. Similarly, higher pain intensity 32,34 and episodic patterns to a lesser reported extent 38 are recognized characteristics of neuropathic pain, so too are recent histories of surgery and chemotherapy, 34,39e41 including the newer generation biologic therapies. 42,43 Our study's strengths include its broad representation of the spectrum of cancer stages, its use of validated assessment tools, and the completeness of data collection.…”
Section: Discussionmentioning
confidence: 99%